The Effect of Bellboy Service Quality on Guest Satisfaction at The Premiere Hotel Padang - Rizki Nurzamil Putra; Trisna Putra (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
This research was initiated because of guest complaints about the service at The Premiere Hotel Padang. The aim is to analyze the effect of service quality on guest satisfaction, and is motivated bythere are still many new employees who have not mastered the applicable SOP, limited bellboy workforce so that when the hotel is full it cannot remind guests to carry out health protocols properly. This type of research is quantitative research in the form of causal relationships. Place of research at Premiere Hotel Padang. The research variables are the independent variable service quality and dependent variable guest satisfaction. The population is guests at The Premiere Hotel Padang. Research respondents totaling 100 people were obtained with a non-probability sampling technique. The instrument is a questionnaire which is arranged according to a Likert scale. Test the instrument by means of testing the validity and reliability test. Data were analyzed with basic statistics of research results and data descriptions. Test requirements analysis using normality test, homogeneity test and linearity test. The result is the Quality of Service category does not agree with the percentage of 44%.R square value 0,382 with sig 0,002<0,05 This means that the effect of service quality on satisfaction is 38.2%, while 61.8% is influenced by other factors that have not been studied in this study;